The idea of creativity - Krausz, Michael, 1942-; Dutton, Denis; Bardsley, Karen (Philosophy of history and culture, 2009)
Seventeen philosophers, scientists and artists consider questions about the intriguing idea of creativity: Is creativity essentially mysterious? Is creativity essentially inspirational or rationalistic? What role does skill play in creativity? What are the criteria of creativity? Should we assign logical priority to creative persons, creative processes, or creative products? How do forms of creativity relate to different domains of human activity? How does creativity relate to self-transformation? How does our knowledge of the circumstances of creativity effect our appreciation of its products.